Frequency and clinical predictors of coronary artery disease in chronic renal failure renal transplant candidates - Seixas, Emerson de Albuquerque; Carmello, Beatriz Leone [UNESP]; Kojima, Christiane Akemi [UNESP]; Contti, Mariana Moraes [UNESP]; Modeli de Andrade, Luiz Gustavo [UNESP]; Maiello, Jose Roberto; Almeida, Fernando Antonio; Martin, Luis Cuadrado [UNESP] (Informa Healthcare, 2015)
Background/aims: Cardiovascular diseases are major causes of mortality in chronic renal failure patients before and after renal transplantation. Among them, coronary disease presents a particular risk; however, risk predictors have been used to diagnose coronary heart disease. This study evaluated the frequency and importance of clinical predictors of coronary artery disease in chronic renal failure patients undergoing dialysis who were renal transplant candidates, and assessed a previously developed scoring system. Methods: Coronary angiographies conducted between March 2008 and April 2013 from 99 candidates for renal transplantation from two transplant centers in Sao Paulo state were analyzed for associations between significant coronary artery diseases (>= 70% stenosis in one or more epicardial coronary arteries or >= 50% in the left main coronary artery) and clinical parameters. Results: Univariate logistic regression analysis identified diabetes, angina, and/or previous infarction, clinical peripheral arterial disease and dyslipidemia as predictors of coronary artery disease. Multiple logistic regression analysis identified only diabetes and angina and/or previous infarction as independent predictors. Conclusion: The results corroborate previous studies demonstrating the importance of these factors when selecting patients for coronary angiography in clinical pretransplant evaluation.
Keywords: Chronic renal failure; Coronary artery disease; Coronary angiography; Cardiovascular disease; Renal transplantation